Standardisation of the 129I, 151Sm and 166mHo activity concentration using the CIEMAT/NIST efficiency tracing method. (March 2016) - Altzitzoglou, Timotheos; Rožkov, Andrej
Abstract: The 129 I, 151 Sm and 166m Ho standardisations using the CIEMAT/NIST efficiency tracing method, that have been carried out in the frame of the European Metrology Research Program project "Metrology for Radioactive Waste Management" are described. The radionuclide beta counting efficiencies were calculated using two computer codes CN2005 and MICELLE2. The sensitivity analysis of the code input parameters (ionization quenching factor, beta shape factor) on the calculated efficiencies was performed, and the results are discussed. The combined relative standard uncertainty of the standardisations of the 129 I, 151 Sm and 166m Ho solutions were 0.4%, 0.5% and 0.4%, respectively. The stated precision obtained using the CIEMAT/NIST method is better than that previously reported in the literature obtained by the TDCR ( 129 I), the 4πγ-NaI ( 166m Ho) counting or the CIEMAT/NIST method ( 151 Sm). Highlights: Standardisation of 129 I, 151 Sm and 166m Ho by Liquid Scintillation Counting. Use of the CIEMAT/NIST efficiency tracing method and the CN2005 and MICELLE2 codes. Complete uncertainty budgets for each radionuclide standardisation. Work performed for the EMRP project "Metrology for Radioactive Waste Management".